Tosse, uma visão do otorrinolaringologista. - Bretan, Onivaldo [UNESP] (My University, 1993)
Persistent cough leads individuals to seek for medical assistance. Clinical investigation, however, may not reveal any alteration within the clinic's sphere of action. Often enough, some professionals treat the symptom as a disease, introducing several medicines, unsuccessfully. The author's experience, as an otolaryngologist, allows to state that many of these professionals ignore the upper aerodigestive tract as a cough-generator site. The present work discusses the alterations on the mentioned tract, which may provoke the cough reflex, reviewing, initially, the cough mechanism and the localization of the specific receptors. Cough is produce by stimulus at the receptor level or far from it. In upper and lower parts of the aerodigestive tract secretions may run to several directions. Secretion from the paranasal sinus is a frequent cause of cough. Acute sinusitis may occur insidiously bringing about the chronification of the inflammation with cough being the only great apparent symptom. Nasal and dental alterations favor sinusal infection. Signs and symptoms, even if minimum, may be detected through an accurate anamnesis. Nasal allergy, laryngitis, post nasal dripping and septal deviation may also produce cough. The ORL examination is, therefore, imperative, and no radiologic examination can substitute for it. An inadequate treatment, particularly of the sinusitis, may bring about a worsening and extension of the initial condition.
Cough: an otorhinolaryngologist's view
Keywords: coughing; human; otorhinolaryngology; pathophysiology; sinusitis; Cough; English Abstract; Human; Otolaryngology; Sinusitis